(untitled) (Journal Of Educational and Psychological Researches, 2017)
The present study aims at finding out the (effect of the Caroll’s pattern on the second intermediate class pupils’ achievement in geography) The partial experimental design of two groups, experimental and control, with pre-post tests is used. The sample is represented in (74) female pupils. The sample is divided into two groups (38) experimental group and (36) control one. The sample is selected from first intermediate class pupils ( Am Salama Secondary School for girls) Baghdad Al-karkh-1, for academic year 2015-2016. The researcher has equalized the two groups in several variables: the previous achievement tests, intelligence, age in months, the scores of geography test of first course